2020
DOI: 10.1021/acs.jpcb.0c02720
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of Insulin Release: Disordered N-Terminal Tail of Kir6.2 Affects Potassium Channel Dynamics through Interactions with Sulfonylurea Binding Region in a SUR1 Partner

Abstract: Inward rectifying potassium ion channels (KATP), sensitive to the ATP/ADP concentration ratio, play an important, control role in pancreatic β cells. The channels close upon the increase of this ratio, which, in turn, triggers insulin release to blood. Numerous mutations in KATP lead to severe and widespread medical conditions such as diabetes. The KATP system consists of a pore made of four Kir6.2 subunits and four accompanying large SUR1 proteins belonging to the ABCC transporters group. How SUR1 affects KAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…The pore diameter at constriction site one ranges from 0.81 to 1.27 Å, in the respective cryo-EM structures. This is in line with previous studies which identified L164 as a narrow, pore-lining site in Kir6.2 ( Loussouarn et al, 2000 ; Loussouarn et al, 2001 ; Kurata et al, 2004 ; Proks et al, 2005 ; Kurata et al, 2006 ; Walczewska-Szewc and Nowak 2020 ). Distances at constriction site 2 range from 0.81 to 1.27 Å, while the pore was slightly wider at I296 (constriction site 3), with distances ranging from 1.5 to 2.9 Å.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The pore diameter at constriction site one ranges from 0.81 to 1.27 Å, in the respective cryo-EM structures. This is in line with previous studies which identified L164 as a narrow, pore-lining site in Kir6.2 ( Loussouarn et al, 2000 ; Loussouarn et al, 2001 ; Kurata et al, 2004 ; Proks et al, 2005 ; Kurata et al, 2006 ; Walczewska-Szewc and Nowak 2020 ). Distances at constriction site 2 range from 0.81 to 1.27 Å, while the pore was slightly wider at I296 (constriction site 3), with distances ranging from 1.5 to 2.9 Å.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, an important limitation of our study concerns the lack of the SUR domain, which was not included in our simulation systems, due to the large system size, poor resolution, and many missing residues of these domains. It has to be noted, however, that the N-terminal transmembrane domain of SUR1 modulates PIP 2 sensitivity in Kir6.2 channels ( Pratt et al, 2011 ; Walczewska-Szewc and Nowak 2020 ). This might explain why no wetting or widening at the uppermost constriction site was observed in our simulations, rendering the channels essentially non-conductive.…”
Section: Resultsmentioning
confidence: 99%
“…The pore diameter at constriction site 1 ranges from 0.81 to 1.27 Å, in the respective cryo-EM structures. This is in line with previous studies which identified L164 as a narrow, pore-lining site in Kir6.2 (Kurata et al 2004; Kurata, Marton, and Nichols 2006; Loussouarn et al 2000, 2001; Proks et al 2005; Walczewska-Szewc and Nowak 2020). Distances at constriction site 2 range from 0.81 to 1.27 Å, while the pore was slightly wider at I296 (constriction site 3), with distances ranging from 1.5 to 2.9 Å.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, an important limitation of our study concerns the lack of the SUR domain, which was not included in our simulation systems, due to poor resolution and many missing residues of these domains. It has to be noted, however, that the N-terminal transmembrane domain of SUR1 modulates PIP 2 sensitivity in Kir6.2 channels (Pratt et al 2011; Walczewska-Szewc and Nowak 2020). This might explain why no wetting or widening at the uppermost constriction site was observed in our simulations, rendering the channels essentially non-conductive.…”
Section: Resultsmentioning
confidence: 99%
“… 30 Such a method is commonly used to enforce a change in the conformational states of proteins. 31 , 32 Details are described in ref ( 33 ). The resulting structure overlaps the target, which was hamster open SUR1 (PDB ID: 6BAA).…”
Section: Methodsmentioning
confidence: 99%